PENGARUH SERVANT LEADERSHIP, TRUSTIN LEADERSHIP DAN KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI PADA KSP â€œKOPDIT MARSUDI MULYOâ€ PUTAT PATUK GUNUNGKIDUL - Safari, Teti (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
The purpose of this study was to determine the effect of Sarvent Leadership, trust in leadership and service quality on the satisfaction of members of the Marsudi Mulyo Patut Gunungkidul Savings and Loan Cooperative (KSP). The population taken was the members of the cooperative savings and loan cooperative (KSP) Kopdit Marsudi Mulyo totaling 73 as samples. Data collection was carried out by distributing questionnaires to respondents. The collection technique used SPSS 17. Based on the results of the study, it was stated that the sarvent leadership variable had a positive and significant effect on member satisfaction because it had a significance value of 0.000 <0.05. The trust in leadership variable has a positive and significant effect on the Member Satisfaction variable because it has a significant value of 0.000 <0.05. And the variable service quality has a positive and significant effect on the variable member satisfaction. This can be seen from the significant quality of service because it has a significant value of 0.086 <0.05.